Quest For Life Reflected In Antoine De Saint- Exupery's The Little Prince Novel (1943): An Existentialist Approach - Sejati., Ardita Kurnia, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2015)
This study is aimed to show The Little Prince quest of life in The Little Prince novel by using existentialist approach. It is done by establishing two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the novel based on the Existentialist Approach. This research is descriptive qualitative research. Type of data of the study is text from two data sources: primary and secondary. The primary data source is the The Little Prince novel by Antoine saint de- Exupery released in 1943. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that characters and characterization, setting (setting of place and setting of time), plot (exposition, complication, climax, resolution, causality, and plausibility), point of view, theme style (grammatical structure, sentence construction, diction) are related to each other and form a unity. Second, based on the Existentialist analysis reflected in the character and characterization in being, existence before essence, consciousness (cogito), freedom to choose, anxiety, transcendence ego, and nothingness, quest for the existence of life lead to meaningful purpose in human's life.